The Performance Evaluation of Catfish Hatchery Business in Maguan Village, Ngajum Subdistrict, Malang Regency, East Java - Nina Widyawati; Anthon Efani; Tiwi Nurjannati Utami (Faculty of Fisheries and Marine Science, Brawijaya University, 2017)
The aims of the research are to know and to analyze the performance of catfish hatchery business in Desa Maguan viewed from the perspective of finance and non finance. The research use survey method with qualitative and quantitative descriptive research. The result show that the business performance is 77,44% in